THE STATE OF TEMPORARY EMPLOYMENT SERVICES IN DEMOCRATIC SOUTH AFRICA (The Pretoria Student Law Review, 2021)
For many years now, South Africa, like many countries has legally recognised labour hiring as a form of employment, through various pieces of legislature. According to section 198(2) of the Labour Relations Act the parties in this tripartite relationship are the temporary employment service is known as the employer, the employee, who is the person who’s been contractually procured for his services, and the client, who is the user enterprise that seeks the services of the temporary employment service. This type of employment has been under public and legal scrutiny for a while now because of malpractice(s) against employees. Trade Unions have called for the total banning of the operation of temporary employment agencies whereas some organisations including the Confederation of Associations in the Private Employment Sector (CAPES) have called for codes of conduct that will regulate the industry. The motor industry has recently banned the operation of temporary employment services in its sector, due to the recent industrial strikes concerning the salaries and wages of employees in the industry. This move has become an exception to section 198. However, will this ban by the motor industry be the beginning of more sectors calling for the ban of temporary employment services in pursuit to being part of the exception? This article will look at the problems faced by temporary employment services in South Africa, the consequences of the lack of enforcement of the laws governing this industry, as well as what South Africa can learn from the international and foreign community.
Keywords: Labour Relations Act; tripartite relationship; labour hiring; temporary employment service; industrial strikes; lack of enforcement of laws